2019
DOI: 10.2196/preprints.17549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Acceptability of a Tablet-Based App to Support Men to Link to HIV Care: Mixed Methods Approach (Preprint)

Abstract: BACKGROUND The poor engagement of men with HIV care is attributed to a number of factors: fear of stigma, masculine representations, concerns related to confidentiality, and the time commitment needed to visit public health clinics. Digital technologies are emerging as an approach to support the engagement of men with care. OBJECTIVE This study aims to deliver a usable and engaging tablet-based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…44 However, some participants did not use the earphones or needed assistance from the study staff to navigate the app. 45 Additionally, due to time constraints for both study staff and participants during household visits, some reported that they did not have sufficient time to explore the app or rushed through navigating the app. 45 Lastly, the number of new HIV diagnoses, and consequently those who were successfully reached and provided with EPIC-HIV 2 was low in this single round of intervention, which would have reduced the power to detect an intervention effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 However, some participants did not use the earphones or needed assistance from the study staff to navigate the app. 45 Additionally, due to time constraints for both study staff and participants during household visits, some reported that they did not have sufficient time to explore the app or rushed through navigating the app. 45 Lastly, the number of new HIV diagnoses, and consequently those who were successfully reached and provided with EPIC-HIV 2 was low in this single round of intervention, which would have reduced the power to detect an intervention effect.…”
Section: Discussionmentioning
confidence: 99%
“…45 Additionally, due to time constraints for both study staff and participants during household visits, some reported that they did not have sufficient time to explore the app or rushed through navigating the app. 45 Lastly, the number of new HIV diagnoses, and consequently those who were successfully reached and provided with EPIC-HIV 2 was low in this single round of intervention, which would have reduced the power to detect an intervention effect. Building upon the high acceptability of the app, strategies to increase the reach and dose, such as offering the app through mobile phones or targeting a larger audience, could be considered in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the process evaluation have been published elsewhere. 38 The trial was registered at the National Institute of Health (ClinicalTrials.gov # NCT03757104), and the complete trial protocol was published elsewhere. 36…”
Section: Trial Designmentioning
confidence: 99%